2021
DOI: 10.1037/xge0000988
|View full text |Cite
|
Sign up to set email alerts
|

Utilitarianism for animals, Kantianism for people? Harming animals and humans for the greater good.

Abstract: Most people hold that it is wrong to sacrifice some humans to save a greater number of humans. Do people also think that it is wrong to sacrifice some animals to save a greater number of animals, or do they answer such questions about harm to animals by engaging in a utilitarian cost-benefit calculation? Across 10 studies (N = 4,662), using hypothetical and real-life sacrificial moral dilemmas, we found that participants considered it more permissible to harm a few animals to save a greater number of animals t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 58 publications
1
21
0
Order By: Relevance
“…Previous studies have suggested that adults exhibit speciesism (Caviola et al, 2019). For example, adults value humans more than animals even in cases in which humans have equal or lower cognitive capacities than animals (Caviola et al, 2020). Thus, one possible explanation of our findings is that children are far less speciesist than adults.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have suggested that adults exhibit speciesism (Caviola et al, 2019). For example, adults value humans more than animals even in cases in which humans have equal or lower cognitive capacities than animals (Caviola et al, 2020). Thus, one possible explanation of our findings is that children are far less speciesist than adults.…”
Section: Discussionmentioning
confidence: 99%
“…This is sometimes referred to as speciesism —a term from philosophy that frames our attitude toward animals as a prejudice analogous to sexism or racism (Singer, 1975). In support of the speciesism hypothesis, studies have shown that factors such as the lesser mental capacities of animals play only a partial role in explaining our preference for humans (Caviola et al, 2020). For example, in cases in which humans with severe cognitive impairment have capacities equivalent to or even lower than some animals, people will nonetheless still value humans more than animals.…”
mentioning
confidence: 99%
“…The significant self-advice difference between dilemmas containing human lives versus nonhuman lives could be evidence that self-choice and advisor participants weigh information differently. Recently, Caviola and colleagues (2021) found support for a multilevel weighted deontology model , which indicates that deontological weights change according to an individual’s perceived moral standing. Of import, humans are thought to have higher moral standing than nonhumans (Caviola et al, 2019); therefore, in response to the moral dilemmas, advisors may be applying different deontological weights for humans and nonhumans in a possibly lexicographic manner, by associating greater deontological weight when deciding for humans and comparatively little for nonhumans.…”
Section: Possible Mechanismsmentioning
confidence: 99%
“…Donors in the developed world, for example, prefer local over foreign charities although charities working in distant poor countries tend to be more effective [13,[25][26][27]. Second, there is biological distance: most people prefer to help humans over animals, even when controlling for perceived cognitive capacity and capacity for suffering [28,29]. The tendency to favor humans over animals is a stable trait that correlates with tendencies that are widely regarded as biases (e.g., racism, sexism) and is reflected in donation behavior (helping humans vs animals) [28].…”
Section: Narrow Moral Circlementioning
confidence: 99%